PERTIMBANGAN HAKIM TERHADAP PELAKU TINDAK PIDANA PENGEDARNARKOTIKA GOLONGAN 1 JENIS SABU (Studi Putusan Nomor 906/Pid. Sus/2024/PN Tjk) - Akbar Ramadhan Gumaz; Zainab Ompu Jainah; Okta Anita (INTELIGENSIA MEDIA, 2025)
This thesis discusses the judge's considerations towards perpetrators of criminal acts against drug dealers of class 1 type of crystal methamphetamine. Narcotics are one of the serious problems faced by society, and crystal methamphetamine dealers are one of the main actors in the illicit trafficking of narcotics. This study aims to analyze and understand how judges in the Indonesian justice system consider various aspects in sentencing perpetrators of drug trafficking crimes, especially crystal methamphetamine. The problem taken in this study is to determine the judge's considerations in making legal decisions and whether factors such as the background of the perpetrator, the nature of the perpetrator in the trial can influence the judge and relevant legal aspects, and what factors cause someone to dare to commit unlawful acts and including the Narcotics Law based on Decision Number: 906 / Pid.Sus / 2024 / PN TJK. The research method used is a qualitative approach with a case study, where data is collected through interviews, observations, and analysis of related documents. The results of the study indicate that there are several factors that encourage someone to finally choose to become a dealer and one of them is the economic factor and the lack of education of the perpetrator, and there are also reasons why someone becomes a dealer is because he is a user as well as environmental factors are also the reason why someone decides to become a dealer and the judge's considerations in deciding the case are the background of the perpetrator, the evidence presented, the role of the defendant and paying attention to whether the defendant is involved in a larger network and considering the nature of the perpetrator during the trial and the cooperation of the perpetrator during the investigation. The suggestion in the study is that there needs to be better cooperation between law enforcement agencies, the government, and civil society organizations in preventing and overcoming narcotics trafficking. Adjustments in legal policies also need to be made to consider the rehabilitation of perpetrators as an alternative to imprisonment, so that perpetrators can reintegrate into society better.